(High Temperature Materials Division J. Bruce Wagner, Jr. Award) Oxygen Non-Stoichiometry of La, Yb, Y, and Ca Doped Cerium Oxide and the Stoichiometric Expansion Coefficient of Yb, Y, and Ca Doped Cerium Oxide. (26th April 2016) - Bishop, Sean R.
Abstract : The oxygen non-stoichiometry (δ) for M0.1 Ce0.9 O1.95-δ (M = La, Yb, and Y), Ca0.1 Ce0.9 O1.9-δ, and undoped ceria are reported at 800 o C and compared with literature results for undoped and Gd doped ceria. Reducibility shows an increasing trend with increasing amount of oxygen vacancies introduced by the dopant. The stoichiometric expansion coefficient for the Yb, Y, and Ca doped samples was evaluated and found to be approximately equal and within the range typically found for ceria. A clear dependence of stoichiometric expansion coefficient on ionic radius or oxygen vacancy concentration was not observed.